Effects of fertility rate on Singapore economy. - Hou, Wai Ling. (2008)
This paper seeks to uncover the economic impacts that chronic fertility decline have on the Singapore economy, and therefore explains the rationale of the Government’s change of stance. In essence, a literature review and regression model is done.